Quality metrics in cardiac catheterization for congenital heart disease: Utility of 30‐day mortality. Issue 1 (7th October 2014) - Backes, Carl H.; Bergersen, Lisa; Rome, Jonathan J.; Batlivala, Sarosh P.; Glatz, Andrew C.; Ovunc, Bugsu; David, Sthuthi; Rivera, Brian K.; Haque, Urbee; Kollins, Kevin; Yin, Han; Holzer, Ralf J.
<x xml:space="preserve">Abstract</x> Objectives: To characterize the frequency and attributability of death among patients who died within 30 days of their cardiac catheterization (30‐day mortality). Background: 30‐day postprocedure mortality is commonly used as a quality outcome metric in national cardiac catheterization registries. It is unclear if this parameter is sufficiently specific to meaningfully capture mortality attributable to cardiac catheterization in patients with congenital heart disease (CHD). Methods: Multicenter cohort study with 3 participating centers. Records were retrospectively reviewed for patients who died within 30 days of catheterization (06/2007‐06/2012). Attributability of death was assigned to each case. Results: A total of 14, 707 cardiac catheterization procedures were performed during the study period. Death occurred within 30 days in 279/14, 707 (1.9%) of cases. Among the patients who died, 53% of cases were emergent or urgent cases. The median age was 4 mos (1 day–45 years). Death was attributable to the catheterization procedure in 29/279 (10%) of cases. Death was attributable to cardiac surgery in 14%, precatheterization clinical status in 34%, postcatheterization clinical status in 22%, and noncardiac comorbidity in 19%. In 1%, death attributability could not be established. Conclusions: While valuable in adult settings, 30‐day mortality is inadequate as a quality metric among patients with CHD undergoing cardiac catheterization. To derive the optimal benefit from catheterization registry data, more robust methodologies to capture procedure‐related mortality are needed. © 2014 Wiley Periodicals, Inc.